1990
DOI: 10.1111/j.1398-9995.1990.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines stimulate the phosphorylation of phosphatidylinositol in rat mast cell granules

Abstract: Rat mast cell granules were obtained by homogenization of highly purified rat mast cells and isolated in a Percoll gradient. Diphosphoinositide (DPI) synthesis in rat mast cell granules was assayed by measuring the incorporation of 32P from [gamma 32P] ATP into DPI in the absence of exogenous phosphatidylinositol (PI). Lipids were isolated with methanol/chloroform/HCl and were separated by thin-layer chromatography on oxalic acid impregnated silica gel plates. DPI areas were identified by staining with iodine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Polyamines are required for DNA synthesis and cell proliferation (58,59), and for synthesis of proline, the precursor for collagen production (60,61). Consistent with the finding of greater arginase activity in asthma in the current study, serum levels of polyamines are elevated in subjects with asthma and in experimental models of asthma (5,(62)(63)(64)(65). Taken together with previous studies, the present cross-sectional observational study identifies alterations of Arg metabolism in asthma.…”
Section: Discussionsupporting
confidence: 78%
“…Polyamines are required for DNA synthesis and cell proliferation (58,59), and for synthesis of proline, the precursor for collagen production (60,61). Consistent with the finding of greater arginase activity in asthma in the current study, serum levels of polyamines are elevated in subjects with asthma and in experimental models of asthma (5,(62)(63)(64)(65). Taken together with previous studies, the present cross-sectional observational study identifies alterations of Arg metabolism in asthma.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, several studies have reported that rat peritoneal tissuetype mast cells [19][20][21] as well as the rat RBL-2H3 cell line [22,23] release ROS into the extracellular milieu in response to a range of stimuli. Swindle et al, [24] reported that Pholasin was not cell-permeable and that it detected release, rather than intracellular ROS.…”
Section: Generation Of Ros By Mast Cellsmentioning
confidence: 80%
“…Recent investigations from our laboratory indicate the presence of increased polyphosphoinositide metabolism in activated rat mast cells (5). Moreover, it has been demonstrated that naturally occurring aliphatic polyamines, such as spermine and spermidine, stimulate the phosphorylation of phosphatidylinositol in rat mast cell granules (6) and induce histamine release from rat mast cells (7). Interestingly, spermine at a concentration of 0.1 nimol/1, which in itself could not cause a significant histamine release, showed a tendency to enhance anti-IgEinduced histamine release from mast cells (7).…”
Section: Discussionmentioning
confidence: 99%
“…Aliphatic polyamines are naturally occurring cations, and their ubiquitous distribution and the complexity of the mechanisms that regulate their intracellular concentrations suggest important roles for these compounds in normal cellular growth and differentiation (4,8). Recent investigations from our laboratory indicate that naturally occurring ahphatic polyamines, such as spermine and spermidine, stimulate the phosphatidyhnositol kinase that catalyzes the formation of phosphatidyhnositol 4-phosphate from endogenous phosphatidyhnositol in rat peritoneal mast cell granules (6). They also induce a significant histamine release from rat peritoneal mast cells (7), suggesting possible involvement of polyamines in allergic reactions.…”
mentioning
confidence: 99%